Invasive micropapillary carcinoma of the mammary gland in humans and canines: Clinicopathological, immunophenotypical and survival approaches. (December 2017) - de Oliveira Gamba, Conrado; Scaratti, Dirceu; de Andrade, Victor Piana; Estrela-Lima, Alessandra; Ferreira, Enio; Cassali, Geovanni Dantas
Abstract: Invasive micropapillary carcinoma (IMPC) is a breast cancer with a proclivity for lymph node metastasis that affects women. In canines, this carcinoma has only recently been reported and appears to have similar histological aspects as its human counterpart. Thus, the aim of the present study was to compare clinicopathological, immunohistochemical and prognostic characteristics of mammary IMPC between humans and canines. In canines, regional metastasis was more frequently observed. Histopathologically, humans and canines predominantly showed a moderate histological grade. The pure subtype and neoplastic emboli were more frequently observed in canines. Regarding immunohistochemical evaluation, most canine and human IMPCs were positive for the estrogen and progesterone receptors. A reversed pattern of epithelial membrane antigen expression and a high proliferation index predominated in both species. The mortality due to the neoplastic disease was more frequently observed in canines (94%) than in humans (4%). Thus, canine IMPCs show a larger tumor size and higher rates of the pure subtype, regional metastasis and mortality than their human counterparts and appear to provide a good spontaneous model for achieving a better understanding of the biological behavior of human IMPCs. Highlights: Human and canine IMPCs reveal frequently lymph node metastasis. Canine IMPCs are more aggressive neoplasms when compared to its human counterpart. Canine IMPCs are a good model to better understand the biology of human IMPCs.